The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.18176/archmeddeporte.00030
|View full text |Cite
|
Sign up to set email alerts
|

Pain catastrophizing in Flamenco dance students at professional dance conservatories

Abstract: Introduction: Flamenco is marked by the deep emotional impression it creates and its percussive footwork steps, performed in traditional high-heeled shoes. It places high demands on the dancer which leads to risks of injury, pain and associated emotional repercussions. Catastrophizing is a key factor determining how the context is valued and pain is experienced. The objectives of this study were: firstly, to analyse the general incidence of catastrophizing among flamenco students and secondly, to determine the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…About "physical" and "biomechanical" aspect as hotspots, there are some main reasons. Flamenco dance has its unique characteristics with strong emotion and the footwork technique (Baena-Chicón, Gómez-Lozano, Cano, & Vargas-Macías, 2021), which requires dancers strike the floor to make a loud and rhythm voice (Vargas-Macías et al, 2021). Therefore, dancers were usually required to have a high level of physical conditions (Forczek, Baena-Chicon, & Vargas-Macias, 2017), there is research indicate that the require is similar to those of elite sports (Pedersen, Wilmerding, Kuhn, & Enciñias-Sandoval, 2001).…”
Section: Table 3 High-yield Regions In the Flamenco Dance Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…About "physical" and "biomechanical" aspect as hotspots, there are some main reasons. Flamenco dance has its unique characteristics with strong emotion and the footwork technique (Baena-Chicón, Gómez-Lozano, Cano, & Vargas-Macías, 2021), which requires dancers strike the floor to make a loud and rhythm voice (Vargas-Macías et al, 2021). Therefore, dancers were usually required to have a high level of physical conditions (Forczek, Baena-Chicon, & Vargas-Macias, 2017), there is research indicate that the require is similar to those of elite sports (Pedersen, Wilmerding, Kuhn, & Enciñias-Sandoval, 2001).…”
Section: Table 3 High-yield Regions In the Flamenco Dance Researchmentioning
confidence: 99%
“…Some articles involved psychological analysis of flamenco participants. There is evidence that shows both students and professionals displayed higher levels of helplessness than those who were only students, and anxiety states which can be triggered by the artistic professional development on stage before spectators may relate to the levels of catastrophism (Baena-Chicón, Gómez-Lozano, Cano, & Vargas-Macías, 2021). Meanwhile, there is research that studied Brazilian female flamenco dancers and indicated 64.7% of participants were not satisfied with their bodies though they had high self-esteem (Nakamura, Juzwiak, de Almeida, & Montesano, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…About "physical" and "biomechanical" aspect as hotspots, there are some main reasons. Flamenco dance has its unique characteristics with strong emotion and the footwork technique (Baena-Chicón, Gómez-Lozano, Cano, & Vargas-Macías, 2021), which requires dancers strike the floor to make a loud and rhythm voice (Vargas-Macías et al, 2021). Therefore, dancers were usually required to have a high level of physical conditions (Forczek, Baena-Chicon, & Vargas-Macias, 2017), there is research indicate that the require is similar to those of elite sports (Pedersen, Wilmerding, Kuhn, & Enciñias-Sandoval, 2001).…”
Section: Table 3 High-yield Regions In the Flamenco Dance Researchmentioning
confidence: 99%
“…Some articles involved psychological analysis of flamenco participants. There is evidence that shows both students and professionals displayed higher levels of helplessness than those who were only students, and anxiety states which can be triggered by the artistic professional development on stage before spectators may relate to the levels of catastrophism (Baena-Chicón, Gómez-Lozano, Cano, & Vargas-Macías, 2021). Meanwhile, there is research that studied Brazilian female flamenco dancers and indicated 64.7% of participants were not satisfied with their bodies though they had high self-esteem (Nakamura, Juzwiak, de Almeida, & Montesano, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Injuries can inhibit career development for dancers and can lead to injured dancers been replaced by healthy dancers (Vassallo et al, 2018) which can influence daily life and mental state (Baena-Chicón et al, 2021). Therefore, investigating the status of flamenco dancers' lower limbs may identify injury risk factors and allow the development of injury prevention programs (Maloney, 2019).…”
Section: Introductionmentioning
confidence: 99%